Best Management Practices and Long-Term Water Quality Trends in the Everglades Agricultural Area - Daroub, Samira H; Van Horn, Stuart; Lang, Timothy A; Diaz, Orlando A (Critical reviews in environmental science and technology, 2011)
The Everglades Agricultural Area (EAA) in South Florida, part of the historical Everglades, was initially drained in the early 20th century for agriculture and flood protection. The organic soils have been subject to subsidence caused by organic matter oxidation. Soils are deeper east of Lake Okeechobee compared to soils south of the lake. The area is mostly planted to sugarcane and other crops such as rice, vegetables, and sod. Concerns about quality of water leaving the EAA led to a regulatory program for mandatory best management practices (BMP) since 1995 to reduce phosphorus (P) loads out of the EAA by 25% compared to historical levels. The program is highly successful, with 100% grower participation and exceeding P load reduction required by law. Trend analysis conducted on selected EAA farms, subbasins, and whole basin show, in general, decreasing trends in P concentrations, drainage flow, and P loads. Differences are noted between farms and subbasins due to factors that include rainfall distribution, water management practices, irrigation water quality, soil type/depth, and cropping systems. Water management practices were the dominant factors affecting P loads out of the EAA. Water management research that targets farms with deeper soils is recommended to achieve additional P load reductions. Other practices to improve BMP performance include minimizing generation and transport of sediments from farm canals. The quality of irrigation water from Lake Okeechobee is of concern of its impact on BMP performance.